Stinging predatory journals: a brief overview and recommendations - Adam Larson; Matan Shelomi (European Science Editing)
Predatory journals exploit the open access model for profit, often publishing papers with minimal or nonexistent peer review. Predatory publishing stings can identify predatory publishers and increase awareness of the problem, but there are no guidelines for effective stings. We propose that stings should include peer review red flags that would stop the sting from being accepted by reputable journals, be followed by a public sting statement to alert others to the predatory journal identified and predatory publishing in general, and avoid both payment to predatory publishers and risk to the stinger.